Effects of ultrasonic treatment on the surface bacteria of Lyophyllum decastes during storage. (January 2023) - Hu, Yuxin; Lin, Xiaotong; Liu, Xinrui; Zhong, Xinyi; Lin, Hailu; Jiang, Danxia; Zhang, Fangyi; Zhong, Xinlin; Jiang, Yuji; Chen, Bingzhi
Graphical abstract: Highlights: Ultrasonic treatment reduces the abundance of Lyophyllum decastes surface bacteria. Ultrasonic treatment has better bacteriostatic effect on surface bacteria of L. decastes. It preserves whiteness index, hardness, and sensory quality during storage. Abstract: This study explores the relationship between the storage quality and bacterial microflora in the mushroom Lyophyllum decastes . The surface bacteria of L. decastes were separated by combining the traditional culture plate separation and 16S rRNA sequencing method, to study the effects of ultrasonic (US) treatment on the surface bacteria of L. decastes during storage. The results demonstrated that Pantoea agglomerans and Pseudomonas fluorescens were among the 15 culturable bacteria isolated with traditional plate method during storage, belonging to 2 phyla and 7 genera. US treatment could inhibit the growth and significantly increase cell membrane permeability, and contents extravasation in P. agglomerans, though its inhibitory effect on P. fluorescens was less. The 16S rRNA sequencing revealed, bacteria from 9 phyla and 35 genera were isolated, and P. fluorescens was the dominant species throughout the storage time. These results indicated that the composition of mushroom surface microflora of Control (CK) and US groups are similar, and the bacterial microflora networks analysis also showed a positive correlation. The KEGG annotation for the functional classification of the bacteria showed that a total of 328 pathways were acquired at the KEGG l3 level, and the relative abundance of membrane transport, amino acid metabolism, carbohydrate metabolism, and energy metabolism pathway was high. Moreover, the relative abundance of the surface bacteria of L. decastes also decreased . Hence, the US treatment had a better bacteriostatic effect, maintained the whiteness index and firmness, and improved the sensory quality of L. decastes during storage.